Effectiveness of a Multidisciplinary Approach Intervention to Improve Blood Pressure Control Among Elderly Hypertensive Patients in Rural Thailand: A Quasi-Experimental Study - Woodham, Nanthakan Sungsuman (J Multidiscip Healthc, 2020)
PURPOSE: Uncontrolled blood pressure among Thai elderly hypertensive patients is a significant public health issue in primary health care facilities under the Universal Health Coverage Scheme in Thailand. This study examines the effectiveness of a multidisciplinary approach intervention to improve blood pressure control among elderly persons in rural Thailand. PATIENTS AND METHODS: This was quasi-experimental study conducted on 200 elderly persons who receive care for hypertension at primary health care facility in rural areas of Thailand. Participants were assigned to either the intervention or control groups. The intervention group was subjected to a multidisciplinary approach intervention program. This program included community-based care for hypertension, family-supportive care for hypertension, antihypertension medication adherence education program, the use of a reminder electronic pill box, and monthly pill counts and blood pressure measurements. The intervention continued for three months. The control group received care for hypertension at the hypertension clinic of the health center. Three measurements were taken at baseline, one month, and three months after the intervention. Data analysis included descriptive statistics and independent sample t-tests. Repeated-measure analysis of variance (ANOVA) and analysis of covariance (ANCOVA) were used to compare the differences between the two groups. RESULTS: At one month and three months after the intervention, the multidisciplinary approach intervention controlled blood pressure more effectively compared with the control group. Furthermore, the intervention group had lower systolic and diastolic blood pressure compared with the control group (P-value < 0.001). CONCLUSION: These results suggest that the multidisciplinary approach intervention can be effective in controlling blood pressure in elderly hypertensive patients. Future studies should investigate a cost-effective means of integrating multidisciplinary approach interventions in routine hypertension care for elderly hypertensive patients.